2020
DOI: 10.3390/molecules25245988
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Effect of Sintering Conditions of Mg0.95Ni0.05Ti3 on Its Physical and Dielectric Properties

Abstract: Mg0.95Ni0.05TiO3 ceramics were prepared by traditional solid-state route using sintering temperatures between 1300 and 1425 °C and holding time of 2–8 h. The sintered samples were characterized for their phase composition, micro-crystalline structure, unit–cell constant, and dielectric properties. A two-phase combination region was identified over the entire compositional range. The effect of sintering conditions was analyzed for various properties. Both permittivity (εr) and Q factor (Qf) were sensitive to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…However, the ratio of (Mg 0.95 Ni 0.05 )TiO 3 phase in the ceramics was decreased due to the increased grain boundary motion with the increasing sintering temperature, as shown in Table 1. Moreover, the (Mg 0.95 Ni 0.05 )TiO 3 had no noticeable impact on the dielectric properties of (Mg 0.95 Ni 0.05 ) 2 TiO 4 in our previous study [19]. Therefore, the influence of the inferior (Mg 0.95 Ni 0.05 )TiO 3 phase can be negligible when the sintering temperature is over 1350 • C. 2.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…However, the ratio of (Mg 0.95 Ni 0.05 )TiO 3 phase in the ceramics was decreased due to the increased grain boundary motion with the increasing sintering temperature, as shown in Table 1. Moreover, the (Mg 0.95 Ni 0.05 )TiO 3 had no noticeable impact on the dielectric properties of (Mg 0.95 Ni 0.05 ) 2 TiO 4 in our previous study [19]. Therefore, the influence of the inferior (Mg 0.95 Ni 0.05 )TiO 3 phase can be negligible when the sintering temperature is over 1350 • C. 2.…”
Section: Resultsmentioning
confidence: 62%
“…Moreover, an inferior (Mg 0.95 Ni 0.05 )TiO 3 phase also appeared during the synthesizing of (Mg 0.95 Ni 0.05 ) 2 TiO 4 , which may be attributed to the effect of the thermal decomposition mechanism [18]. However, the slight (Mg 0.95 Ni 0.05 )TiO 3 -doped (Mg 0.95 Ni 0.05 ) 2 TiO 4 possess a comparable performance, with an ε r value of 17.2, a Qf value of 180,000 GHz, and a τ f value of −45 ppm/ • C [19], compared to those of the pure (Mg 0.95 Ni 0.05 ) 2 TiO 4 composition [17].…”
Section: Introductionmentioning
confidence: 99%
“…Materials possessing the following dielectric properties are suitable for dielectric resonators [5][6][7][8]: (1) Permittivity (ε r ) > 20: The permittivity is an essential factor for component size reduction. (2) Quality factor (tanδ, the inverse of the dielectric loss) > 30,000 (GHz): Lower insertion loss and steeper cut-off can be obtained due to a higher Qf value, which ensured the lower dielectric loss of components.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the partial replacement of Mg by B 2+ (B 2+ = Co, Ni, and Zn) increases the structural densification and upgrades the dielectric performance of MgTiO 3 . (Mg 0.95 B 2+ 0.05 )TiO 3 with an ilmenite-type structure has been documented to possess excellent dielectric performance [8,13,14] [22][23][24][25][26][27]. In this paper, with partial substitution of Mg 2+ (0.072 nm) by Ni 2+ (0.069 nm), the microstructure densification of (Mg 0.6 Zn 0.4 ) 0.95 Ni 0.05 TiO 3 was observed, and microwave dielectric performance of that was also further improved compared to (Mg 0.6 Zn 0.4 )TiO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…To upgrade the dielectric performances of MgTiO 3 -based ceramics, some studies focus on substituting Mg with M 2+ (M 2+ = Co, Ni, and Zn) and the (Mg 0.95 M 2+ 0.05 )TiO 3 ceramics preserve the ilmenite-type structure [ 11 , 12 ]. Shen et al [ 13 ] first reported Mg 0.95 Ni 0.05 TiO 3 with a Q f of 192,000 (GHz), ε r ~17.35, and τ f of –47 (ppm/°C) for the samples sintered at 1350 °C and 4 h. The main disadvantage of (Mg 0.95 M 2+ 0.05 )TiO 3 ceramics is their high negative τ f and, hence, difficulty to be practically utilized in microwave applications. Therefore, some researchers improved the microwave dielectric properties of (Mg 0.95 M 2+ 0.05 )TiO 3 by mixing τ f compensator [ 14 ].…”
Section: Introductionmentioning
confidence: 99%